Research in the social scientific study of religion / Volume 17 - Piedmont, Ralph L. (Research in the social scientific study of religion, 2007)
An analysis of conversion narratives of Jehovah's Witnesses and their relationships to stages of religious judgment /Ines W. Jindra --Intolerance toward others and belief in an active Satan /Keith M. Wilson, Jennifer L. Acord, and Ronan S. Bernas --Transgression and transformation : spiritual resources for coping with a personal offense /Kelly M. McConnell, Maria R. Gear, and Kenneth I Pargament --Religion and ethnicity among Irish Americans in Savannah, Georgia /William L Smith and Barbara Hendry --The relationship between parental images and ministerial job satisfaction among Anglican clergymen in England /Douglas W. Turton and Leslie J. Francis --Prayer, purpose in life, personality and social attitudes among non-churchgoing 13- to 15-year-olds in England and Wales /Leslie J. Francis and Mandy Robbins --Biblical interpretive horizons and ordinary readers : an empirical study /Andrew Village --A factor analysis of the Fetzer/NIA Brief Multidimensional Measure of Religiousness/Spirituality (MMRS) /Ralph L. Piedmont, Anna Teres Mapa, and Joseph E.G. Williams --Variant uses of religious beliefs to justify social attitudes /Mark M. Leach, Jacob J. Levy, and Lisa Denton --The role of religiosity in parenting young children /Bonnie C. Nicholson and Leah McMorris --Heaven's gates and hell's flames : afterlife beliefs of Catholic and Protestant undergraduates /Julie Juola Exline and Ann Marie Yali.